Nacidas digitales - Bordes-Cabrera, Isabel (Anuario ThinkEPI, 2015)
Reseña del informe: Redwine, Gabriella et al. (2013). Born digital: guidance for donors, dealers, and archival repositories. http://www.clir.org/pubs/reports/pub159/pub159.pdf